Pancreatic exocrine carcinoma in a lohmann brown chicken - Aydogan, A; Avcı, H; Birincioğlu, B; Birincioğlu, SS (Journal of the Hellenic Veterinary Medical Society, 2024)
A 23-month-old lohmann brown breed chicken showed symptoms of anorexia, depression and diarrhea before dying. It presented to the pathology laboratory for necropsy. The necropsy confirmed serosal, white and nodular widespread tumor infiltrations in different sizes in the intestines and periton adjacent to the pancreas. In the histological examination, poorly differentiated epithelial cells were seen to form tubular structures in the pancreatic tissue located between the duodenum. According to pathology, this case was diagnosed as pancreatic exocrine carcinoma. This case report provides histologic descriptions of the pancreatic exocrine carcinoma in a chicken that have been reported extremely rare in poultry and pet birds.